Mucinous cystadenoma of ovary with third degree uterovaginal prolapse in postmenopausal woman: a rare case report - H. K., Aishwarya; Singh, Y. Ajitkumar; Devi, K. Tarunibala; Bandi, Krupa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Mucinous tumours of the ovary represent a spectrum of neoplastic disorders, including benign mucinous cystadenoma, pseudomyxoma peritonei, mucinous tumors of low malignant potential (borderline), and invasive mucinous ovarian carcinoma. These tumors are related closely to each other and are distinct from other histologic subtypes of epithelial ovarian neoplasms from a clinical, histologic, and molecular standpoint. Mucinous cystadenoma of ovary presenting with 3rd degree uterovaginal prolapse is extremely rare. This case highlights the importance of choosing the appropriate route of approach and about maintaining the gynae oncological safety. In our case, total abdominal hysterectomy with bilateral salpingo oophorectomy with anterior colporrhaphy with McCalls Culdoplasty with Moschowitz repair and posterior perineorrhaphy was performed.